Spatial Differentiation and Elements Influencing Urban Resilience in the Middle Reaches of the Yangtze River under the COVID-19 Pandemic - Xin Hou; Qianli Ma; Xuan Wang (Discrete Dynamics in Nature and Society)
Since the outbreak of COVID-19 in Wuhan City, Hubei Province, in December 2019, the middle reaches of the Yangtze River became the key areas of the spread of the pandemic and association, and also as the urban economic recovery process after the pandemic eased, it provided an excellent opportunity to research urban resilience. From the viewpoint of urban social-ecological system resilience in public health emergencies, this study comprehensively applies the spatial econometrics, geodetector model, and other methods to investigate the urban resilience level, spatial differentiation, and dominant elements in the middle reaches of the Yangtze River under the impact of the pandemic. This study would aid in providing a scientific basis for sustainable spatial planning and governance. The results demonstrated that the urban resilience in the middle reaches of the Yangtze River had notable spatial agglomeration features, eight elements including tertiary industry proportion possessed a robust explanatory power to the spatial differentiation of urban resilience, and the explanatory power was markedly enhanced after the interaction between influential elements of economic and ecological subsystems. Thus, to upgrade the system cycle mechanism and augment the endogenous power for urban development, we need to focus more on the flow of innovative elements in central cities, the optimization of ecological and safe spatial patterns in Hunan and Hubei Provinces, and the innovation of sustainable supply chain in the entire region.